2014
DOI: 10.5852/ejt.2014.71
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Andean butterfly Eryphanis zolvizora group (Lepidoptera, Nymphalidae): one or several species?

Abstract: Eryphanis zolvizora (Hewitson, 1877) is a rare Andean endemic butterfly, described from Bolivia, which has been historically classified either as a unique species, or as part of a group of three allopatric species from Bolivia, Ecuador and Colombia. In this paper, the group is revised using more than 200 specimens housed in 34 European, and North and South American public and private collections. For the first time, the presence of the group in Western Ecuador and Venezuela is confirmed, and important data on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 1,416 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…This implies that male genitalia and wing color (including androconial scales) vary independently across the geographical range of the genus as a whole. Blandin et al (2014) found that wing color patterns, hind wing shape, and male genitalia did not vary in concert across the range of Eryphanis zolvizora (Hewitson) sensu lato (Brassolini). Those authors regarded wing color as a unifying character for zolvizora, while variation in wing shape and male genitalia were used at the subspecific level (nominal zolvizora, opimus and greeneyi).…”
Section: Discussionmentioning
confidence: 92%
“…This implies that male genitalia and wing color (including androconial scales) vary independently across the geographical range of the genus as a whole. Blandin et al (2014) found that wing color patterns, hind wing shape, and male genitalia did not vary in concert across the range of Eryphanis zolvizora (Hewitson) sensu lato (Brassolini). Those authors regarded wing color as a unifying character for zolvizora, while variation in wing shape and male genitalia were used at the subspecific level (nominal zolvizora, opimus and greeneyi).…”
Section: Discussionmentioning
confidence: 92%